Ice Cream Cone Product Development Based On Purple Sweet Potato (Ipomoea batatas L.) (Study Substituted Purple Sweet Potato Flour and Baking Time) - insiah, halimatul; pulungan, maimunah hindun; rahmah, nur lailatul (University of Brawijaya, 2020)
This study aims to dcidee the subtitution of the use of purple sweet potato flour and baking time in making of ice cream cones and knowing consumer acceptance of ice cream cone purple sweet potato. Experiments using Least Significance Different (LSD) consisted of 2 factors. The first factor is the subtitution for purple sweet potato flour (P) and the second factor is baking time (W). The P factor has 4 levels, namely 100%, 75%, 50%, and 25%. The W factor has 3 levels, namely 20 minutes, 25 minutes, and 30 minutes. Parameters of observation based on yield, thickness, fracture, resistance of ice cream cone, water content test, protein content, and reducing sugar content. The best treatment results were followed by organoleptic tests using a hedonic scale (color, flavor, taste, and texture) carried out by 30 semi-trained panelists. Physical and chemical data were analyzed by ANOVA variance (Î± = 0.05) and if significantly different continued with LSD test (Î± = 0.05). The selection of the best treatment used the Multiple Attribute method. Organoleptic data were analyzed by Friedman test (Î± = 0.05). The best treatment results were obtained subtitution of 75% purple sweet potato flour with 20 minutes baking time. The best treatment has characteristics of water content of 4.07%, yield of 0.98%, fracture of 0.67N, thickness of 2.67mm, resistance of cone 85 minutes, protein content of 27.4656 mg/L, reduced sugar content of 3.8931 mg/L, and organoleptic test results with a scale of 1-5 were obtain on average color 3.73, flavor 3.57, taste 3.57, and texture 2.97.Â Keywords:Â Purple Sweet Potato Flour, Quality of Ice Cream Cone, Wheat Flour